2015
DOI: 10.1016/j.earlhumdev.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Are sporadic fidgety movements as clinically relevant as is their absence?

Abstract: There is no evidence that the occurrence of occasional isolated fidgety bursts indicates a milder type of CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 31 publications
0
51
0
1
Order By: Relevance
“…Infants with abnormal FMs may develop normally, 6,18,24,25 but could also develop CP. 6,15 Some studies documented an association between abnormal FMs and coordination difficulties and/or fine manipulative disabilities. 17,18,25 Recently, an exceedingly high rate of abnormal FMs was described in infants who were later diagnosed with autism spectrum disorder.…”
Section: Normal Fmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Infants with abnormal FMs may develop normally, 6,18,24,25 but could also develop CP. 6,15 Some studies documented an association between abnormal FMs and coordination difficulties and/or fine manipulative disabilities. 17,18,25 Recently, an exceedingly high rate of abnormal FMs was described in infants who were later diagnosed with autism spectrum disorder.…”
Section: Normal Fmsmentioning
confidence: 99%
“…When infants focus on the environment, their FMs are mainly displayed in the hips and ankles, not so much in the shoulders and wrists. 14,15 Intermittent FMs (score: +) Intermittent FMs occur in all body parts, though with longer pauses (up to 10 s), which creates the impression that FMs are only present during half of the observation time. 14,15 Sporadic FMs (score: +−) Isolated fidgety bursts of 1 s to 3 s are interspersed with long pauses of up to 1 min.…”
Section: Normal Fmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study of infants with cerebral palsy found that motor abilities did not differ between infants with sporadic or absent FM. 24 Studies of longterm outcomes are needed to appreciate the neurodevelopmental implications of sporadic-versus-absent FM, because their underlying mechanisms of injury may be different. Future research directions will require detailed motor assessment and correlation with long-term gross, fine, and oral motor control and language, and adaptive competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating whether there are differences in GMs between different ethnic or cultural groups are, to the best of our knowledge, not available. Most studies have been performed in Europe, although more studies are now coming also from Brazil, China, Iran and South Africa (9,(16)(17)(18) . It has further been claimed that GMA studies have a risk for bias because study samples are selected retrospectively, based on available video recordings rather than well-defined high-risk cohorts.…”
Section: (8)mentioning
confidence: 99%